The Relationship Between the Implementation of Phase I Cardiac Rehabilitation and the Outcome of Patients Undergoing Coronary Artery Bypass Surgery in West Java Hospitals - Indah Dwi Astuti; M. Rizki Akbar; Aan Nuraeni; Romalina Romalina (Alliance oh Health Activists (AloHA), 2021)
The implementation of phase I cardiac rehabilitation in patients undergoing Coronary Artery Bypass Surgery is useful to assist the recovery process and improve the quality of patient outcomes. However, the implementation of cardiac rehabilitation in Coronary Artery Bypass Surgery patients is still unknown. Thus, this study aims to identify how the implementation of phase I cardiac rehabilitation and its relationship to the outcome of patients undergoing coronary artery bypass surgery in hospitals in West Java. The research design was a cohort study. Sampling was done by purposive sampling method and obtained 24 respondents. Data were collected by observing the implementation of phase I cardiac rehabilitation and patient outcome sheets. The data were analyzed descriptively, followed by the Kendall Tau and Spearman Rank tests. The results showed that the implementation of phase I cardiac rehabilitation was in the sufficient and less categories (50%), the length of stay in the intensive room was prolonged (70.8%), postoperative length of stay was in the normal category (95.8%), there were postoperative complications (20.8%), functional capacity in the category of light intensity activity (83.3%), and knowledge in the good category (66.7%). The results of the analysis of the relationship between the implementation of phase I cardiac rehabilitation with patient outcomes (length of stay in the intensive care unit and postoperatively, postoperative complications, functional capacity, and knowledge) showed p value > 0.05. Furthermore, it was concluded that there was no relationship between the implementation of phase I cardiac rehabilitation and patient outcomes. However, clinically it does not mean that phase I cardiac rehabilitation has no impact on patient outcomes. This may occur because the implementation of cardiac rehabilitation is still in the sufficient and insufficient category, as a result of the lack of clarity of the SOPs used. So it is recommended to evaluate and improve SOPs on cardiac rehabilitation so that it is in harmony with patients undergoing Coronary Artery Bypass Surgery. Keywords: Coronary artery bypass surgery; patient outcome; phase I cardiac rehabilitation